2012
DOI: 10.1002/etc.2074
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant‐mobilizing capability of fullerene nanoparticles (nC60): Effect of solvent‐exchange process in nC60 formation

Abstract: Abstract-Fullerene nanoparticles (nC 60 ) in aqueous environments can significantly enhance the transport of hydrophobic organic contaminants by serving as a contaminant carrier. In the present study, the authors examine the effect of the solvent-exchange process on nC 60 aggregate formation and, subsequently, on nC 60 's contaminant-mobilizing capability. A series of nC 60 samples were prepared using a modified toluene-water solvent-exchange method through the inclusion of a secondary organic solvent in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Multi-walled nanotubes have been also used for sorption of antibiotics [59], herbicides [60] or nitrogen and phosphorus in wastewater [61]. On the other hand, fullerenes as well as CNTs exhibit a mobilization potential for various organic pollutants [62], such as lindane (agricultural insecticide) [63] and persistent polychlorinated biphenyls [64]. The significant advantages of CNMs comprise their enormous surface area, mechanical and thermal stability, high chemical affinity for aromatic compounds [65], and potential antibacterial properties (described below).…”
Section: Environmental Applications Of Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Multi-walled nanotubes have been also used for sorption of antibiotics [59], herbicides [60] or nitrogen and phosphorus in wastewater [61]. On the other hand, fullerenes as well as CNTs exhibit a mobilization potential for various organic pollutants [62], such as lindane (agricultural insecticide) [63] and persistent polychlorinated biphenyls [64]. The significant advantages of CNMs comprise their enormous surface area, mechanical and thermal stability, high chemical affinity for aromatic compounds [65], and potential antibacterial properties (described below).…”
Section: Environmental Applications Of Carbon-based Nanomaterialsmentioning
confidence: 99%
“…The environmental health and safety risks of CNPs in society have thus become a serious concern in academia. Assessing the risks of CNPs requires more insight into the critical physicochemical processes affecting their behavior in the environment [7,8]. Physicochemical interactions are of particular concern, because CNPs with high surface reactivity are able to interact with a variety of compounds in the aquatic environment, such as natural organic matter [9][10][11], surfactants [10][11][12], and environmentally relevant organic acids [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that even the lowest concentration of nC 60 significantly enhanced the dispersal of both PCB and phenanthrene, whereas columns containing only various types of DOM had no effect on contaminant transport (Zhang et al, 2011b). The enhanced contaminant mobilisation ability of nC 60 relative to naturally occurring DOM was attributed to its unique porous structure and surface enthalpies of interaction, which generate a large sorption affinity together with an irreversibly or slowly desorbable fraction of adsorbed phenanthrene/PCBs (Hofmann and von der Kammer, 2009;Zhang et al, 2011b;Wang et al, 2012a). CNMs may therefore be much more efficient at enhancing the mobility of contaminants than natural colloidal materials.…”
Section: Cnm-hoc Mobilitymentioning
confidence: 99%